Critical reflections on second-generation mindfulness-based interventions. (November 2022) - Smith, Zachary T.
Abstract: Objectives: The purpose of this paper is to provide a critical introduction on Second-Generation Mindfulness-Based Interventions (SG-MBIs) to sport and performance psychology scholars and practitioners. Method: This essay is written as a commentary on Roychowdhury et al.'s, (2021, this issue) article in this issue. Specifically, I apply theoretical insights from Roychowdhury et al., (2021, this issue) to the practical model of SG-MBIs. Results: I find that SG-MBIs attempt to respond to ethical concerns with the ways that mindfulness has been commodified, secularized, and universalized through appeals to cultural authenticity. Discussion: While acknowledging the cultural contexts from which practices like mindfulness have been taken is important, appeals to cultural authenticity often reproduce fixed and essentializing constructions of culture and are easily coopted by neoliberal multiculturalism. Conclusion: As sport and performance psychology professionals reflect on the next generation of mindfulness-based interventions, it will be important to attend to the contextual flexibility of neoliberalism to universalize and essentialize.